2012
DOI: 10.1590/s1983-51752012000100006
|View full text |Cite
|
Sign up to set email alerts
|

Rede hemostática: uma alternativa para a prevenção de hematoma em ritidoplastia

Abstract: Auersvald A et al. Hemostatic net: an alternative for the prevention of hematoma in rhytidoplasty Rede hemostática: uma alternativa para a prevenção de hematoma em ritidoplastia ABSTRACT Background: Hematoma is the most common postoperative complication of rhytidoplasty. Its occurrence increases morbidity and impairs recovery. Internal sutures to close detached areas are used in abdominoplasty to prevent seromas. Taking this into account and in order to reduce the number of patients with hematomas post rhytido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 24 publications
0
16
0
1
Order By: Relevance
“…Several authors use general anesthesia in their services 3,4,8,10 . The anesthesia performed in this study was sedation associated with local infiltrative anesthesia with lidocaine, also used by other authors 2,11 . Endotracheal intubation and reflexes triggered by general anesthesia can cause arrhythmias, reflex hypertension and bleeding, with hematoma formation.…”
Section: Discussion Discussion Discussion Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors use general anesthesia in their services 3,4,8,10 . The anesthesia performed in this study was sedation associated with local infiltrative anesthesia with lidocaine, also used by other authors 2,11 . Endotracheal intubation and reflexes triggered by general anesthesia can cause arrhythmias, reflex hypertension and bleeding, with hematoma formation.…”
Section: Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…Many surgical approaches have been suggested for the prevention of this complication, most only of local action, such as external stitches 2 , use of suction drains 4 , tumescent infiltration 4 , tissue glues 5 , dissection with ultrasonic instruments 6 and internal adhesion stitches 7 .…”
Section: Introduction Introduction Introduction Introduction Introducmentioning
confidence: 99%
“…Dentre todas, a complicação mais frequente continua sendo o hematoma que, em algumas situações, pode comprometer a vascularização do retalho levando a necrose tecidual e exigir reabordagem cirúrgica [3][4][5][6][7][8][9][10][11][12] .…”
Section: Introductionunclassified
“… 4 In 2012 based on the concept of mechanical closure, Auersvald et al described a surgical procedure of transcutaneous continuous and transfixing sutures of skin flaps in rhytidoplasty, creating a hemostatic net that leads to almost total occlusion of the treated area. 5 They found that this technique was an efficient method for the prevention of early hematomas, without an increase in ischemia or necrosis of flaps. 4 In 2018, the same authors described the use of this method in facelift surgery, with the conclusion that hemostatic net is a safe and effective method to reduce hematoma in the early postoperative period by not altering the perfusion of the flaps.…”
mentioning
confidence: 99%
“… 4 This is achieved because the suture performed provides an almost total occlusion of the surgical area and avoids fluid accumulation. 5 However, the use of this procedure has not been described in split-thickness skin grafts in burn patients.…”
mentioning
confidence: 99%